2003
DOI: 10.1007/s00425-003-1087-3
|View full text |Cite
|
Sign up to set email alerts
|

Photon- and carbon-use efficiency in Ulva rigida at different CO 2 and N levels

Abstract: The seaweed Ulva rigida C. Agardh (Chlorophyta) was cultured under two CO(2) conditions supplied through the air bubbling system: non-manipulated air and 1% CO(2)-enriched aeration. These were also combined with N sufficiency and N limitation, using nitrate as the only N source. High CO(2) in U. rigida led to higher growth rates without increasing the C fixed through photosynthesis under N sufficiency. Quantum yields for charge separation at photosystem II (PSII) reaction centres (phi(PSII)) and for oxygen evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 35 publications
(46 reference statements)
3
50
2
1
Order By: Relevance
“…An increase in N uptake is a common response found in macroalgae cultured at high CO 2 levels. Under such growing conditions, Gracilaria sp., Gracilaria chilensis, Porphyra leucosticta, Ulva rigida, Hizia fusiforme, and Gracilaria lemaneiformis showed enhancement of NO 3 − uptake and higher nitrate reductase activity (Gao et al 1993;Mercado et al 1999;Gordillo et al 2001Gordillo et al , 2003Zou 2005;Xu et al 2010), and this uptake enhancement was suggested to play a major role as more nitrogen is required to support higher growth rates, as it appears to be the case also for Hypnea. From a practical point of view, these results suggest that intensive culture of H. spinella operated in biofilters might be enhanced by CO 2 supply to generate higher biomass productivities and better nitrogen biofiltration efficiencies.…”
Section: Discussionmentioning
confidence: 96%
“…An increase in N uptake is a common response found in macroalgae cultured at high CO 2 levels. Under such growing conditions, Gracilaria sp., Gracilaria chilensis, Porphyra leucosticta, Ulva rigida, Hizia fusiforme, and Gracilaria lemaneiformis showed enhancement of NO 3 − uptake and higher nitrate reductase activity (Gao et al 1993;Mercado et al 1999;Gordillo et al 2001Gordillo et al , 2003Zou 2005;Xu et al 2010), and this uptake enhancement was suggested to play a major role as more nitrogen is required to support higher growth rates, as it appears to be the case also for Hypnea. From a practical point of view, these results suggest that intensive culture of H. spinella operated in biofilters might be enhanced by CO 2 supply to generate higher biomass productivities and better nitrogen biofiltration efficiencies.…”
Section: Discussionmentioning
confidence: 96%
“…N supply influences the protein and pigment contents, and the C uptake rate in many types of seaweeds, including the genus Ulva (Gómez-Pinchetti et al 1998). Seaweeds under HNS from fishpond effluents benefit not only from a rich source of ammonia but also from an important and free source of dissolved inorganic C (DIC) coming from fish respiration that becomes available for algal photosynthesis (Mata et al 2007 of Ulva may also be related to high DOC excretion, which Gordillo et al (2003) reported in Ulva that was subjected to increased CO 2. Organic C release has been suggested as an effective mechanism of maintaining the C and N balance in algae in response to low CO 2 levels, although it was an inefficient response to N limitation (Gordillo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Seaweeds under HNS from fishpond effluents benefit not only from a rich source of ammonia but also from an important and free source of dissolved inorganic C (DIC) coming from fish respiration that becomes available for algal photosynthesis (Mata et al 2007 of Ulva may also be related to high DOC excretion, which Gordillo et al (2003) reported in Ulva that was subjected to increased CO 2. Organic C release has been suggested as an effective mechanism of maintaining the C and N balance in algae in response to low CO 2 levels, although it was an inefficient response to N limitation (Gordillo et al 2003). In addition, high DIC may alleviate photoinhibition because it promotes diminished photodynamic photoinhibition by dissipating excess light as was reported in Cyanobacteria (Qiu & Liu 2004) and terrestrial plants (Hymus et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced growth rate of U. prolifera might be attributed to the energy saved due to the downregulated CCM operation as well as nitrogen metabolism. Elevated CO 2 concentrations stimulated the uptake of NO 3 2 in another Ulva species, Ulva rigida (Gordillo et al, 2001), and enhanced the activity of nitrate reductase in U. rigida (Gordillo et al, 2001(Gordillo et al, , 2003 and Ulva linza (data not shown).…”
Section: Possible Mechanisms and Implicationsmentioning
confidence: 93%